MEDIATING ROLE OF PSYCHOLOGICAL WELL-BEING IN THE RELATIONSHIP BETWEEN FAMILY FUNCTIONING AND INTERNET ADDICTION AMONG YOUTH IN KLANG VALLEY, MALAYSIA - Ho Meng Chuan; Jas Laile Suzana Jaafar; Ng Zi Sze (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Current research aims to explore psychological well-being as the mediating role in the relationship between family functioning and internet addiction among youth in Klang Valley, Malaysia. With the emergence of the positive psychology field in recent years, the focus of research practice has shift from remediating and studying psychological deficits and disability, to the exploration and promoting of psychological well-being while enhancing human strengths. In relation, it is critical to understand risk factors and underlying mechanism through a positive characteristics approach for Internet addiction among youth in order to develop effective preventive and intervention measures. This cross-sectional study includes 130 youth participants who are located in Klang Valley, aging between 18 to 24. A quantitative approach is adopted by collecting data of respondent’s level of family functioning, psychological wellbeing and internet addiction through survey forms on online platforms. Current research findings indicate there is a positive and significant relationship between family functioning and psychological wellbeing (r = 0.385, p<0.001), while negative significant relationship was indicated in the relationship between family functioning and internet addiction (r = -0.230, p<0.01), psychological wellbeing and internet addiction (r = -0.409, p<0.001). Furthermore, the data indicated that psychological wellbeing was proven to mediate the relationship between family functioning and internet addiction, suggesting that family functioning predicts one’s level of psychological well-being, which then continues to play and important rule in influencing internet addiction. Current research findings implies that family environments and interactions greatly influence the development of one’s psychological state, and further influences addictive/problematic behavior.